Child Violence in the Household Sphere in Kasu Village, Belakang Padang District, Batam City - Anggrainy, Novita; Alawiyah, Nur Sahadatul; Casiavera, Casiavera (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2024)
This research aims to determine child violence in the household sphere in Kasu Village, Rear Padang District, Batam City. Where currently there is an increase in the rate of violence against children in Indonesia, this research also aims to determine the impact that occurs due to violence and is analyzed using sociological theory, namely social control theory. This research uses qualitative research methods by means of interviews and collecting data from the internet. Acts of violence committed against children can cause pain, both internal and external injuries to the child. Violence against children can also hinder children's growth and development. Emotional, physical violence or chronic neglect can inhibit the growth of a child's brain and organs, increase the risk of diseases triggered by stress and hinder cognitive and social development which will ultimately lead to anxiety disorders, depression, behavioral disorders and poor academic achievement.